Principialismo bioético y biojurídico: ¿necesitan la bioética y el bioderecho europeos un marco diferente de principios? (2020)
Toe four principies of biomedical ethics are widely used in the world for bioethical deliberation. Therefore, it is understood that these theoretical guides are useful for the analysis and resolution of particularly complex ethical controversies arising in clinical and biomedical fields. This paper unfolds an analysis of the basic universal principies, the common universal morality, and sorne features of each principie. Toen it discusses sorne problems posed by critics of European biolaw who have provided alternative frameworks of principies that are nonuniversal to culture. Finally, it shows how universal moral principies are connected to human rights, how rules and rights are specified to become detailed and practical for certain moralities, and how these ideas are connected with problems of justification in bioethics and biolaw.